Large-scale scene real-time infrared simulation based on texture blending. Issue 4 (14th November 2016) - Wang, Yuye; Zhang, Guofeng; Hu, Xiaoguang
Abstract : Purpose: Infrared simulation plays an important role in small and affordable unmanned aerial vehicles. Its key and main goal is to get the infrared image of a specific target. Infrared physical model is established through a theoretical research, thus the temperature field is available. Then infrared image of a specific target can be simulated properly while taking atmosphere state and effect of infrared imaging system into account. For recent years, some research has been done in this field. Among them, the infrared simulation for large scale is still a key problem to be solved. In this passage, a method of classification based on texture blending is proposed and this method effectively solves the problem of classification of large number of images and increase the frame rate of large infrared scene rendering. The paper aims to discuss these issues. Design/methodology/approach: Mosart Atmospheric Tool (MAT) is used first to calculate data of sun radiance, skyshine radiance, path radiance, temperatures of different material which is an offline process. Then, shader in OGRE does final calculation to get simulation result and keeps a high frame rate. Considering this, the authors convert data in MAT file into textures which can be easily handled by shader. In shader responding, radiance can be indexed by information of material, vertex normal, eye and sun. Adding the effect of infrared imaging system, the final radiance distribution is obtained. At last, the authors get infrared scene by converting radiance to grayscale. Findings: In the fragment shader, fake infrared textures are used to look up temperature which can calculate radiance of itself and related radiance. Research limitations/implications: The radiance is transferred into grayscale image while considering effect of infrared imaging system. Originality/value: Simulation results show that a high frame rate can be reached while guaranteeing the fidelity.